Assessment of the effectiveness and the initial cost efficiency of hot recycled asphalt using polymer modified bitumen - Ali Almusawi; Sarmad Shoman; Andrei P. Lupanov (Case Studies in Construction Materials, 2023)
The drastic increase in environmental concerns and increasing costs of road construction materials necessitate evaluating some alternative solutions. One of the most suitable alternatives is recycling old asphalt pavement to produce reclaimed asphalt pavement (RAP). The RAP materials have been commonly combined with asphalt mixtures during pavement construction. Incorporating RAP material should demonstrate an equivalent or better performance than conventional asphalt mixtures. Conversely, the inclusion of RAP mainly needs to improve performance compared to conventional asphalt mixtures. The key issue of using RAP is to restore the loss properties of aged materials and normally asphalt Agent Rejuvenator (ARA) was used. Also, adding polymers with RAP into the asphalt mixture becomes necessary to obtain the required performance. This study investigated the RAP effects of elastomeric polymer on the performance of the asphalt mixture following Russian standards (GOST). The impact of using PMB with RAP material on the asphalt mixture’s performance was primarily considered by employing tests that can reveal the adhesion property. Additionally, the performance of the pavement was evaluated in terms of strength and low-temperature cracking. For this purpose, numerous test methods were implemented to appraise the asphalt performance, such as compressive strength, moisture susceptibility, shear resistance, tensile strength, porosity of the mineral particles, and residual porosity. The results indicated that the overall performance of the asphalt mixtures prepared with RAP and combined with polymer depicted a better performance. Moreover, the initial construction cost for each asphalt composition was estimated and compared. The utilization of PMB increased the cost of the asphalt mixture. However, such an increase in the cost would lead to an increase in the overall performance, especially for RAP mixtures.